(untitled) (Вестник КазНУ. Серия Востоковедения, 2016)
Тарихи дереккөздерде ХХ ғасырдың алғашқы он жылдығы шығыс елдерінде ояну, өзін-өзі тану, ұлт- азаттық қозғалыс кезеңі ретінде сипатталады. Мақалада М. Хадидің әдебиет пен баспасөз әлеміне өткенге дейін- гі шығармашылығына қысқа шолу жасалған. The article overviews the period until Hady’s coming to literature and art world. It explores the environment in which the poet was born and rose. The article gives information about the poet’s family tree, his childhood and early youth years. It examines the causes that facilitated Hady’s growing up as a personality ad artist in a provincial city like Shamakhi.